2011
DOI: 10.1007/s00348-011-1075-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the uncertainty of astigmatism-μPTV, stereo-μPIV, and μPIV

Abstract: Astigmatism or wavefront deformation, microscopic particle tracking velocimetry (A-lPTV) (Chen et al. in Exp Fluids 47:849-863, 2009; Cierpka et al. in Meas Sci Technol 21:045401, 2010b) is a method to determine the complete 3D3C velocity field in micro-fluidic devices with a single camera. By using an intrinsic calibration procedure that enables a robust and precise calibration on the basis of the measured data itself (Cierpka et al. in Meas Sci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…(19) was presented there with a minus before the expression for (a result of a sign error in Eqn. (21) of that paper).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(19) was presented there with a minus before the expression for (a result of a sign error in Eqn. (21) of that paper).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental investigations have shown that μPIV [11][12][13] and PTV 14,15 are powerful tools for analysing 2D microchannel acoustophoresis. Fully 3D particle tracking has been demonstrated using μPIV with depth of correlations 16 and astigmatism particle tracking velocimetry [17][18][19] . On the other hand, numerical simulations of acoustophoretic motion of microparticles can provide efficient prediction of experiments and provide effective guidance and optimization on the design of acoustofluidic devices to enhance or improve experiments.…”
Section: Introductionmentioning
confidence: 99%
“…More details about calibration and uncertainty of this technique, as well as comparison with other whole-field velocimetry methods for microflows, can be found in Refs. [34,35].…”
Section: Methodsmentioning
confidence: 99%
“…In the middle, stereoscopic measurements are presented and the region of the downward flow was well captured. Although great care was taken to align the system, the focal planes of both cameras differ by several micrometers as outlined in Cierpka et al (2011b). Thus the in-plane velocity corresponds to different regions in the volume.…”
Section: Imaging Based On Aberrations (Astigmatism)mentioning
confidence: 99%
“…Nevertheless, it has to be stated that the uncertainty of a single PTV measurement is higher than for the correlation-based methods, where six to ten particle images contribute to one vector estimation. If six to ten PTV data points are averaged, the uncertainty usually decreases below the value for correlation-based methods (Sato et al 2003;Cierpka et al 2011b). Another advantage of particle tracking methods over correlation-based methods arises regarding instationary or pulsatile flows.…”
Section: Tracking or Correlationmentioning
confidence: 99%